Evaluation of the Biodiversity Offsetting Pilot Programme - Baker,J; Sheate,WR; Bennett,T; Payne,D; Tucker,G; White,O; Forrest,S (2016)
The evaluation project of the biodiversity offsetting pilot programme was a two year study commissioned by Defra which began in July 2012, undertaken by Collingwood Environmental Planning (CEP) in partnership with the Institute for European Environmental Policy (IEEP). Evidence from the pilot programme suggests that whilst biodiversity offsetting has the potential to deliver improvements in biodiversity outcomes it will require additional resources and ecological expertise in local authorities to deliver it and in instances where residual biodiversity loss is identified will increase costs overall for developers compared to current practice. It is likely that it would, at best, deliver only marginal benefits in terms of streamlining the planning process for agreeing compensation for biodiversity loss.